Differential dynamics of the mammalian mRNA and protein expression response to misfolding stress - Cheng, Zhe; Teo, Guoshou; Krueger, Sabrina; Rock, Tara M; Koh, Hiromi WL; Choi, Hyungwon; Vogel, Christine (Molecular systems biology, 2016)
The relative importance of regulation at the mRNA versus protein level is subject to ongoing debate. To address this question in a dynamic system, we mapped proteomic and transcriptomic changes in mammalian cells responding to stress induced by dithiothreitol over 30 h. Specifically, we estimated the kinetic parameters for the synthesis and degradation of RNA and proteins, and deconvoluted the response patterns into common and unique to each regulatory level using a new statistical tool. Overall, the two regulatory levels were equally important, but differed in their impact on molecule concentrations. Both mRNA and protein changes peaked between two and eight hours, but mRNA expression fold changes were much smaller than those of the proteins. mRNA concentrations shifted in a transient, pulse‐like pattern and returned to values close to pre‐treatment levels by the end of the experiment. In contrast, protein concentrations switched only once and established a new steady state, consistent with the dominant role of protein regulation during misfolding stress. Finally, we generated hypotheses on specific regulatory modes for some genes. Synopsis The contribution of mRNA and protein level regulation in the mammalian endoplasmic reticulum stress response is deconvoluted by analyzing time‐series protein and matching mRNA concentrations with a new statistical tool. Protein and mRNA concentrations are quantified at different time points, generating a high‐confidence dataset of 1,237 genes/mRNAs. A new statistical tool quantifies the contribution of regulatory processes and shows that mRNA and protein level regulation play similarly important roles. mRNA and protein level regulation have different dynamics: mRNA concentrations spike in their change and return to pre‐perturbation levels, while protein concentrations switch in their behavior and reach a new steady‐state. Hypotheses on modes of regulation for several groups of genes are presented. Graphical Abstract The contribution of mRNA and protein level regulation in the mammalian endoplasmic reticulum stress response is deconvoluted by analyzing time‐series protein and matching mRNA concentrations with a new statistical tool.